Considerations and challenges in developing novel long-acting antiretrovirals modalities for treatment and prevention of HIV-1 infection: a regulatory perspective. Issue 1 (January 2020) - Sampson, Mario R.; Troy, Stephanie B.; Belew, Yodit; Arya, Vikram; Struble, Kimberly A.
Abstract : Purpose of review: Outline some regulatory considerations and scientific challenges related to the development of long-acting antiretrovirals (ARVs) for the treatment and prevention of HIV-1 infection. Recent findings: Poor adherence to oral ARV regimens continues to pose challenges for effective treatment and prevention of HIV-1 infection. The development of long-acting ARV modalities for treatment and prevention of HIV-1 infection is emerging as a promising alternative to the current treatment and prevention paradigm and has gained considerable interest. Summary: The development of long-acting ARVs can present some unique drug development challenges. Advance planning and prioritization of studies early in development can facilitate the development of long-acting ARVs for the prevention and treatment of HIV-1 infection for all populations, including pediatric patients and pregnant women.